'If It Ain't Broke, Don't Explain It': The Influence of Visual and Verbal Information about Prior Use on Consumers' Evaluations of Refurbished Electronics. (4th July 2018) - Mugge, Ruth; de Jong, Wytske; Person, Oscar; Hultink, Erik Jan
Abstract: Refurbishment presents opportunities for designers to improve the sustainability of new and old products via an experiment and post hoc interviews, this research investigates and explores how information about prior use – offered in a visual (signs of wear and tear) or verbal (textual description) form – influences consumers' evaluations of refurbished products. The findings show that visual information about prior use has a negative effect on consumers' evaluations of refurbished electronics. Furthermore, presenting consumers with verbal information on prior use can negatively affect consumers' evaluations of a refurbished product if no signs of wear and tear are present because it confuses consumers. If signs of wear and tear are present, verbal information about prior use will not influence consumers' evaluations.